Contract Farming’s Impact on Coffee Farmers' Adaptation Strategies To Climate Change in East Java - Rahmadhani, Putri Auliya; Toiba, Hery; Rahman, Moh Shadiqur; Isaskar, Riyanti (Universitas Negeri Gorontalo, 2024)
Contract Farming is considered to be able to increase farmers' yields and income. In addition, another factor that influences is socio-demographic factors, so this research contributes as a reference in coffee farmers' decision-making in choosing adaptation strategies. This research also supports the long-term sustainability of farming to address climate change by supporting the thirteenth Sustainable Development Goals (SDGs) related to climate change mitigation by increasing effective planning and management capacities related to climate change, especially in the agricultural sector in Indonesia. This research was conducted in August 2022 in Pasuruan and Malang, East Java Province. Respondents were determined by Multistage Random Sample Procedure with a total of 100 coffee farmers. From the interview data of 100 coffee farmers in East Java, it was found that the majority of farmers had an understanding of climate change from three indicators: changes in rainfall, temperature, and length of the rainy season. The analysis results showed that Contract Farming influenced farmers' decision to adapt to climate change. In addition, socio-demographic factors that influenced the decision to adapt were the age of the farmer, but its effect was negative, meaning that the younger the age of the farmer, the higher the chance of implementing adaptation strategies. The findings indicate that both Contract Farming and socio-demographic factors are crucial in shaping the adaptation strategies of coffee farmers in response to climate change. This research highlights the importance of promoting Contract Farming as a means to enhance farmers' resilience to climate impacts.